Sistem Monitoring Penggunaan Air Kamar Kos - Rahmi Eka Putri; Nefy Puteri Novani; Fathonah Ghaniyyah (CHIPSET, 2023)
A dormitory is a temporary residence for college students in which they are charged with a certain cost for a certain period of time. The payment for water usage in a dorm includes bathrooms that use PDAM (municipal waterworks). The management of water usage in the dorms is not recorded properly due to the absence of a flow meter in the water pipelines. Monthly water usage in each dormitory room remains uncertain depending on the tenant's need. Therefore, a system was designed to monitor the water usage in dormitory rooms. This system relies on a waterflow sensor component to measure water discharge, an LCD to display a real-time volume and costs, a solenoid valve to stop the water flow when the bill is due, a relay to control the work of the solenoid valve, and ESP32 to process data includes discharge data, volume data, and cost data. These data are sent to the server and stored in a database. Then, the water usage and the monthly cost can be accessed on the website. The system adds a lithium battery, a TP4056 charger module, and a boost converter. The testing was done by designing 3 tools with the same components and functions. The error value on device 1 is 0.5%, device 2 is 0.2%, and device 3 is 0.1%. The success ratio of each function of the system as a whole is 100%.